Identification of Leakage Points and Evaluation of Leakage Parameters Based on Photoelectric Absorption Cross-Section Index - SUN Yuhong; ZHANG Zhihu; XU Jingkang; TAN Weixiong; ZHANG Hao; ZHANG Lei (Cejing jishu)
Lost circulation can increase operational costs, delay project schedules, and influence the response of logging data to formation information through plugging fluids. The tertiary sandstone and mudstone formations in the Bohai area have severe and high frequency lost circulation, some wells with large loss scale leading to the occurrence of loss of return. Accurately locating the leakage interval and predicting the leakage scale, and then conducting targeted research on vulnerable formations, can provide risk warning for later drilling. The photoelectric absorption cross-section index logging curve is used to accurately locate the leakage interval, and its good correlation with instantaneous leakage rate is used to predict the leakage rate. A multi mineral model analysis method is proposed to calculate the relative volume content of barite in the formation, and the leakage amount is calculated by combining the relative volume content of barite with the actual content in the mud. Field applications in several major oil fields in the Bohai area have shown that the calculated leakage rate and amount using the photoelectric absorption cross-section index have relatively small errors compared to the actual data provided on site. The method of using the photoelectric absorption cross-section index to locate the leakage interval, calculate the leakage rate and leakage amount in the article can be used for identifying the leakage point and evaluating the leakage parameters of the well.